The Role Of The Government In The Impact Of Hospital Hazardous Toxic Waste Pollution In Ponorogo - KARIZ, Sela Angelita; PRASETYO, Yogi (Protection: Journal Of Land And Environmental Law, 2025)
In Indonesia, the COVID-19 pandemic is closely linked to the rise in infectious waste produced by the general public and medical professionals. Assuming that many individuals are tainted Coronavirus, the medical clinics limit can influence and how much irresistible waste produced is increment. Irresistible waste remembers for the Hazardous Toxic Waste (B3) squander classification, which contains unsafe and harmful materials that can contaminate, harm, and jeopardize the climate, wellbeing, and the endurance of living things. Ponorogo Regency, which is known as a "red zone" for the spread of COVID-19, is unavoidably affected by Hazardous Toxic (B3) waste. With the expansion in that measure of Hazardous Toxic (B3) squander, the public authority job is expected to satisfy the prudent rule and closeness standard of B3 squander the board. As the mandatory environmental affairs executor, DLHK Ponorogo, the regional government must address Hazardous Toxic (B3) waste management issues at the regional level.